2016
DOI: 10.4184/asj.2016.10.6.1141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High-Riding Vertebral Artery and Morphometry of C2 Pedicles Using a Novel Computed Tomography Reconstruction Technique

Abstract: Study DesignCross-sectional, matched-pair comparative study.PurposeTo determine whether a thin-sliced pedicular-oriented computed tomography (TPCT) scan reconstructed from an existing conventional computed tomography (CCT) scan is more accurate for identifying vertebral artery groove (VAG) anomalies than CCT.Overview of LiteraturePosterior atlantoaxial transarticular screw fixation and C2 pedicle screws can cause vertebral artery (VA) injury. Two anatomic variations of VAG anomalies are associated with VA inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 26 publications
(73 reference statements)
1
35
1
10
Order By: Relevance
“…In the published literature, the incidence of HRVA in the normal population ranged from 10.1% to 32%. 6,13,[24][25][26] However, the incidence increased enormously to 50%-70% in patients with AA subluxation, rheumatoid arthritis, or congenital skeletal anomalies (e.g., os odontoideum, Down syndrome, basilar invagination, and Klippel-Feil syndrome). 2,15,31,32 The issue of HRVA was particularly concerning in candidates for AA fixation, because these diseases frequently coincided with AA subluxation.…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature, the incidence of HRVA in the normal population ranged from 10.1% to 32%. 6,13,[24][25][26] However, the incidence increased enormously to 50%-70% in patients with AA subluxation, rheumatoid arthritis, or congenital skeletal anomalies (e.g., os odontoideum, Down syndrome, basilar invagination, and Klippel-Feil syndrome). 2,15,31,32 The issue of HRVA was particularly concerning in candidates for AA fixation, because these diseases frequently coincided with AA subluxation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the anatomical history of VA, there are two anatomic variations associated with VA injury: the first is high-riding VA (HRVA), which increases the risk of VA injury during C1-2 transarticular screw fixation, (1,3,9,13); and the other is a narrow pedicle that increases VA injury risk in C2 pedicle screwing (27).…”
Section: █ Discussionmentioning
confidence: 99%
“…C2 pedicular screw placement has a more superior and medial trajectory according to transarticular screw placement, which decreases the risk of VA injury (18,27); however, several studies have also found that the anatomical risk of VA injury does not significantly differ between these two techniques…”
Section: █ Conclusionmentioning
confidence: 99%
“…Following the above-mentioned data, Roy Camille et al successfully used C2 pedicle as an insertion point without any neurovascular deficit 39) . However, the vertebral artery (VA) injury with C2 pedicle screw is 5.3%-21% 40,41) .…”
Section: Morphometric Analysis and Surface Landmarksmentioning
confidence: 99%
“…The two anatomic variations associated with VA injury are high-riding VA and narrow C2 pedicle, and the chances of VA injury are more in the latter. The prevalence of high-riding VA is 16.54% 41) . Stanescu et al, in their cadaveric study, mentioned that there is a slight increase in the pedicle height width and length and a decrease in the transverse angle of 4°-6°between adjacent C5-C7 vertebral levels 42) .…”
Section: Morphometric Analysis and Surface Landmarksmentioning
confidence: 99%